Historia y patrimonio monumental. El Castillo Forga de Mollendo - Cabanillas Delgadillo, Virgilio Freddy (2022)
This article is dedicated to a monument and symbol of the city of Mollendo, the castle of Jose Miguel Forga. The building is a National Cultural Heritage and is quite damaged by time, neglect and vandalism. Its condition is a current issue for the patrimonial problematic, due to the fact that the people of Mollendo are determined to restore it and enhance its value. In order to place the monument in context, we used diverse sources that allow us to reconstruct the history of Mollendo, in addition to the in situ recognition of the city, the Forga Castle, and the related buildings.